Clinical utility of skin biopsy detection of phosphorylated alpha-synuclein in an outpatient practice - Todd Levine; Roy Freeman; Nicole Murray; Alexandria Swanson; Colin T. Gibbons; Jason Crowell; Justin Phillips; Christopher H. Gibbons (Frontiers in Neurology, 2026)
Introduction The neurodegenerative disorders characterized by deposition of phosphorylated alpha-synuclein (P-SYN) include Parkinson’s disease (PD), multiple system atrophy (MSA) and dementia with Lewy bodies (DLB). Diagnosis of synucleinopathies in clinical practice has been enhanced by recent updates to diagnostic guidelines. Despite these advances, many patients still fall between diagnostic guideline criteria creating challenges to clinical care. Methods This was a retrospective chart review of patients seen in an outpatient private practice. The objective of this study was to determine the impact of skin biopsy detection of phosphorylated alpha-synuclein (P-SYN) in the clinical care of patients with movement or cognitive symptoms in whom a synucleinopathy was part of the differential diagnosis. The clinical diagnosis and treatment plan before, and after, skin biopsy detection for P-SYN was determined through detailed chart extraction, with ICD-10 codes used to define clinical diagnosis. Results One hundred patients with suspected neurodegenerative disease were included in the chart review, 47 presenting with tremor, 18 with gait dysfunction, 11 with rigidity or bradykinesia and 24 with cognitive dysfunction. After skin biopsy testing for P-SYN, 60% of patients had a change in their ICD-10 documented diagnosis and 91% had a change to their clinical treatment plan. Conclusion In patients with suspected neurodegenerative disease, skin biopsy detection of P-SYN supported changes in the diagnostic impression or management in the majority of patients in this study. These findings support the growing role of diagnostic biomarkers in the diagnosis and management of patients with suspected neurodegenerative synucleinopathies.